2017
DOI: 10.1186/s12884-017-1464-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of perinatal care services from the user’s perspective: a Dutch study applies the World Health Organization’s responsiveness concept

Abstract: BackgroundThe concept of responsiveness was introduced by the World Health Organization (WHO) to address non-clinical aspects of service quality in an internationally comparable way. Responsiveness is defined as aspects of the way individuals are treated and the environment in which they are treated during health system interactions.The aim of this study is to assess responsiveness outcomes, their importance and factors influencing responsiveness outcomes during the antenatal and delivery phases of perinatal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 34 publications
6
25
0
1
Order By: Relevance
“…In previous quantitative studies, this domain performed better than other domains and was judged to be more important than the other domains within the category ‘client orientation’ (also see Box 1). [27, 49] Possible explanations for these differences in study outcomes are the differences in used study designs. The aforementioned studies used questionnaires and structured interviews, which required participants to rate the ‘confidentiality’ domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous quantitative studies, this domain performed better than other domains and was judged to be more important than the other domains within the category ‘client orientation’ (also see Box 1). [27, 49] Possible explanations for these differences in study outcomes are the differences in used study designs. The aforementioned studies used questionnaires and structured interviews, which required participants to rate the ‘confidentiality’ domain.…”
Section: Discussionmentioning
confidence: 99%
“…In that study the ‘client orientated’ category was found less important than the ‘respect for persons’ domains. [27]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They called a free mobile phone number, and spoke to a trained nurse specialist/practitioner to consult maternal and newborn care practices, including a prenatal and postnatal health care and healthrelated issues, neonatal care, their mental health problems, and non-clinical aspects, such as health consultations, immunization integration and family planning. 13 The PPHSN project also provided information for supporting raising a child (the peer support and medical information, knowledge and skills related to a child's developmental needs, emotional support, education, or sensitive lifestyle issues with parents) by nurse specialists. The participants can freely choose one of the three services, including telephone, mobile phone and social networking sites (SNS, email and line devices).…”
Section: Methodsmentioning
confidence: 99%
“…Berdasarkan hasil penelitian yang ditemukan salah satu penyebab ketidakpuasan ibu hamil dalam pelayanan asuhan kehamilan yaitu waktu menunggu (Adeyinka et al, 2017;Chemir et al, 2014;Ejigu et al, 2013;Nwaeze et al, 2013). Waktu yang diperlukan untuk menghadiri pemeriksaan kehamilan menjadi kunci penentu kepuasan antara peserta dalam penelitian, waktu yang dihabiskan bepergian ke klinik, waktu tunggu di klinik (van der Kooy et al, 2017). jumlah waktu yang dihabiskan dengan dokter (Bahadoran, Fahami, & Mohamadirizi, 2014) dan waktu di ambil dari kerja ke pelayanan.…”
Section: Lama Waktu Menungguunclassified